The Power of the Central Bank of Brazil in a Financialised Economy: an institutionalist and Foucauldian analysis - Jaime Marques Pereira; Miguel Bruno; Stéphane Longuet (Revue de la Régulation)
This article attempts to understand political economy by explaining the ambivalence of the economic policy that successfully reconciled redistribution and orthodoxy in Brazil, under the governments led by the Workers’ Party – until that reconciliation proved unsustainable. The analysis combines institutional macroeconomics with a sociological perspective on economic policy instrumentation. The former points out how the distributive purpose became unsustainable, once the financialisation of the capital accumulation process was only limited – but not fundamentally questioned. The latter approach characterises a cognitive lock-in of the developmental State’s improvement. We show that this lock-in was an incremental transformative result of liberal governmentality devices, which redirected the central bank to a new function of gathering together what can be called an instrumental coalition that gave a veto power to financial interests. The central bank has therefore been a crucial institution in a government of the population, in the sense given by Foucault to this concept.